2022
DOI: 10.18844/cjes.v17i5.7304
|View full text |Cite
|
Sign up to set email alerts
|

School connectedness, school climate and emotional and behaviour disorders in students: Examining relationships

Abstract: Students with emotional and behaviour disorders (EBDs) have challenging school connectedness experiences related to their social, behaviour and academic problems. They need accommodative school climate. Therefore, it is necessary to know the relationship between variations in EBDs, school connectedness and school climate. This was a survey research on students with EBDs (N = 60) from 14 inclusive elementary schools. Questionnaires about EBD types, school connectedness and school climate were filled out by teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The school climate will influence the school connection of students. High levels of problem behavior among students were found to be correlated with low school connectedness and problems in school climate [35].…”
Section: ) Discussionmentioning
confidence: 95%
“…The school climate will influence the school connection of students. High levels of problem behavior among students were found to be correlated with low school connectedness and problems in school climate [35].…”
Section: ) Discussionmentioning
confidence: 95%
“…As mentioned, teacher stress can have negative effects on student relationships. In addition, research examining the influence of classroom management practices has revealed that implementing active and interactive learning, support services, and positive emotional feedback can increase overall connectedness and engagement (Mahabbati et al, 2022). Displaying the potential benefits of measuring feelings of school connectedness more frequently to determine which practices and emotions may have an effect on overall feelings of school connectedness.…”
Section: Theoretical Framing Of Teacher Emotion In a Dynamic Environmentmentioning
confidence: 99%